2022
DOI: 10.20527/jee.v3i2.5039
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Based University: Case Study Approach

Abstract: Because the college administration was critical in the development of student entrepreneurship competency, effective policy models were required. Entrepreneurial-based university (EBU) is breaking into one of the chance-leading strategies of developing an effective entrepreneurial development program within a spiritual religious framework. The purpose of this study is to examine how college entrepreneurship management is implemented in West Sumatra province to foster student entrepreneurship. The research was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…This is supported by Hyler's and Prasetyo research, which identifies the problems as a lack of budget dollars, a lack of facilities, limited quality, a lack of excitement and drive, poor innovation, and a lack of enthusiasts. This can be seen in Hyler and Prasetyo studies as well (Darling-Hammond & Hyler, 2020;Prasetyo et al, 2022).…”
Section: Indtroductionmentioning
confidence: 60%
“…This is supported by Hyler's and Prasetyo research, which identifies the problems as a lack of budget dollars, a lack of facilities, limited quality, a lack of excitement and drive, poor innovation, and a lack of enthusiasts. This can be seen in Hyler and Prasetyo studies as well (Darling-Hammond & Hyler, 2020;Prasetyo et al, 2022).…”
Section: Indtroductionmentioning
confidence: 60%
“…The results are supported by Ahwarumi, Prastyo and Hamzah research and revealed that e-commerce/ economic digitalization in generating entrepreneurs along with pesantren ecosystem where this research was conducted. (Ahwarumi & Sawarjuwono, 2017;Hamzah et al, 2022;Prasetyo, Novita, et al, 2022) Pesantren institutions must deal with a wide range of issues, including management, technology, and Shariah law. To ensure the efficacy and integrity of these financial contracts in the digital realm, a delicate balance between these intricate facets is required.…”
Section: Key Factors and Strategiesmentioning
confidence: 99%
“…By equipping individuals with knowledge, skills, and competencies, education enhances their productivity and employability (Solesvik, 2013). Well-educated individuals are more likely to secure higher-paying jobs, contribute to technological advancements, and foster innovation and entrepreneurship (Darmanto & Pujiarti, 2020;Prasetyo et al, 2022;Rashid, 2019).…”
Section: Introductionmentioning
confidence: 99%